Evaluation of S-substituted-2-mercaptobenzimidazole analogs for urease inhibitory and DPPH radical scavenging potential: synthesis, bioactivity, and molecular docking study - Ata, Amber; Khan, Khalid Mohammed; Lateef, Mehreen; Salar, Uzma; Ayaz, Anwar *; Wadood, Abdul; Rehman, Ashfaq Ur; Hameed, Shehryar; Zafar, Fatima; Taha, Muhammad; Perveen, Shahnaz (Springer, 2023)
Several S-substituted-2-mercaptobenzimidazole derivatives 1–34 were synthesized by reacting 2-mercaptobenzimidazole with a variety of substituted benzyl bromide and characterized with the help of various spectroscopic techniques. All synthetic compounds were evaluated for urease inhibitory and DPPH radical scavenging activities. Compounds showed significant to moderate urease inhibitory activity in the range of IC50 = 16.8 ± 0.76–74.3 ± 0.72 µM, in comparison with the standard thiourea (IC50 = 22.4 ± 0.29 µM). It is worth stating that all molecules exhibited noteworthy DPPH radical scavenging potential with IC50 values of 15.5 ± 0.58 to 89.3 ± 0.12 µM when compared with the standard butylated hydroxy anisole BHA (IC50 = 44.2 ± 0.45 µM). A structure–activity relationship (SAR) was presented by analyzing the impact of varying substitutions on urease inhibitory potential. A molecular docking study was done to streamline the binding interactions of ligands (synthetic molecules) with the active pocket of urease enzyme. In addition, cytotoxicity of the most potent compounds 1–4, 14, 18, 20, 28, and 32, was also evaluated, and all were found to be non-cytotoxic.